Peroxides with antiplasmodial activity inhibit proliferation of Perkinsus olseni, the causative agent of Perkinsosis in bivalves - Araujo, Nuna C. P. (2014)
Perkinsus olseni, the causative agent of Perkinsosis, can drastically affect the survival of target marine mollusks, with dramatic economic consequences for aquaculture. P. olseni is a member of the Alveolata group, which also comprises parasites that are highly relevant for medical and veterinary sciences such as Plasmodium falciparum and Toxoplasma. P. olseni shares several unique metabolic pathways with those pathological parasites but is not toxic to humans. In this work, six antimalarially active peroxides, derived from the natural product artemisinin or synthetic trioxolanes, were synthesized and tested on P. olseni proliferation and survival. All peroxides tested revealed an inhibitory effect on P. olseni proliferation atmicromolar concentrations. The relevance of the peroxide functionality on toxicity and the effect of Fe(II)-intracellular concentration on activity were also evaluated. Results demonstrated that the peroxide functionality is the toxofore and intracellular iron concentration also proved to be a crucial co-factor on the activation of peroxides in P. olseni. These data points to a mechanismof bioactivation in P. olseni sharing similaritieswith the one proposed in P. falciparumparasites. Preliminary studies on bioaccumulation were conducted using fluorescent-labeled peroxides. Results show that synthetic trioxolanes tend to accumulate on a vacuolewhile the labeled artemisinin accumulates in the cytoplasm. Preliminary experiments on differential genes expression associated to Fe(II) transport protein (Nramp) and calcium transport protein (ATP6/SERCA) were also conducted by qPCR. Results point to a fourfold increase in expression of both genes upon exposure to trioxolanes and approximately twofold upon exposure to artemisinin derivatives. Data obtained in this investigation is relevant for better understanding of the biology of Perkinsus andmay also be important in the development of new strategies for Perkinsosis prevention and control.